All the flowers are dying : a Matthew Scudder crime novel - Block, Lawrence, 1938- (Harper Collins, 2005)
A man in a Virginia prison awaits execution for three horrific murders he must have committed but swears he didn't . . . An aging investigator in New York City has seen too much and lost too much -- and is ready to leave the darkness behind . . . But a nightmare is coming home -- because a brilliant, savage, patient monster has unfinished business in the big city . . . and a hunger that can be satisfied only by fear and the slow, agonizing death of Matthew Scudder and the woman he loves.